Corruption in Tax and Taxing the Corruption - R. Pazhanisamy (ZBW – Leibniz Information Centre for Economics, 2019)
Most of the countries in the world face corruption and struggling against to it in many aspects. Due to various loopholes and institutional inefficiencies it continues to be pressing issues which affects public in various dimensions. The long existence of corruption around the world made an illusion to the policy makers and public as it is unavoidable and adjustable. This creates an intuition to esquire into what makes the corruption market successful all over the world for many centuries and what Economic theory is operate behind it. In this paper an inquiry is made into how the corruption market works effectively without any intervention. It also explore the possibility of the Ronald Coase theory's to control the corruption and justifies what intervention is needed to achieve optimal amount of corruption. It concludes that to achieve the optimal amount of corruption in the society all farms of corruptions has to be internalized by introducing a permit and tax for corruption.
Keywords: B21; B41; D03; D47; G02; G18; G28; H26; I38; 330; Corruption in Tax; taxing the Corruption; Coase theorem and tax; tax evasion; breaking the tax evasion using Coase theorem; internalizing the externalize of corruption